Community-Based Pyrolysis Training and Technology Transfer for Sustainable Biomass Utilization in Metut Village - Anne Hadiyane; Alfi Rumidatul; Anca Awal Sembada; Hadimanah Fikrudien Bahtiar; Atmawi Darwis; Mustika Dewi; Imra Imra (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Metut Village, Mentarang Hulu District, Malinau Regency, North Kalimantan, possesses abundant woody biomass residues that remain largely underutilized despite their potential economic and environmental value. Simultaneously, local communities face challenges related to low soil fertility and limited success in agarwood (Aquilaria spp.) seed germination. This community service program aimed to introduce pyrolysis technology for converting woody biomass into biochar and liquid smoke while strengthening local capacity through training and technology transfer. By converting biomass residues that were previously left unmanaged or openly burned into valuable products, the program directly contributes to more sustainable biomass waste management at the village level. The three-day program involved 25 participants, including farmers, agarwood cultivators, village officials, women engaged in agriculture, and village youth. Activities comprised educational workshops, practical demonstrations, hands-on training, and the donation of a portable pyrolysis unit. Program effectiveness was evaluated through pre-test and post-test assessments and observation of participants’ practical performance. Results demonstrated a significant increase in knowledge, with average scores rising from 34.2% before training to 82.7% after training, reflecting a marked enhancement in community capacity to independently manage biomass resources. All participants successfully operated the pyrolysis unit during practical sessions. A demonstration run using 12 kg of dry woody branches yielded approximately 3.2 kg of biochar and 2.1 L of liquid smoke, both promising for improving soil fertility and supporting agarwood cultivation. The donated equipment and operational manual provide a practical, replicable foundation for continued community-led biochar and liquid smoke production, supporting the long-term sustainability of biomass utilization and value-added agricultural applications.